Relevansi Moderasi Beragama dengan Penerapan Nilai Aswaja dalam Kepemimpinan Pendidikan di Indonesia - Santoso, Renafa Pinky (Maliki Interdisciplinary Journal, 2025)
In educational institutions, leadership plays a very important role in instilling inclusive, contextual and moderate Islamic values to students. In the midst of the current rampant radicalism and intolerance, it is necessary to strengthen the values of Ahlussunnah wal Jama'ah (Aswaja) in leadership, especially in education. Values such as tawassuth (moderate), tasamuh (balanced), and I'tidal (fair) are a strong foundation for creating a harmonious and peaceful educational atmosphere. This study aims to examine the concept and practice of Islamic educational leadership based on Aswaja and its relevance in supporting religious moderation programs in Indonesia. This study uses a literature study method with a descriptive qualitative approach. The results of the study indicate that Aswaja-based leadership is able to be the vanguard in realizing Islamic education that is adaptive, inclusive, and in line with national values.